2015
DOI: 10.1063/1.4936554
|View full text |Cite
|
Sign up to set email alerts
|

Insights on proximity effect and multiphoton induced luminescence from gold nanospheres in far field optical microscopy

Abstract: Gold nanoparticles can be visualized in far-field multiphoton laser-scanning microscopy (MPM) based on the phenomena of multiphoton induced luminescence (MIL). This is of interest for biomedical applications, e.g., for cancer diagnostics, as MPM allows for working in the near-infrared (NIR) optical window of tissue. It is well known that the aggregation of particles causes a redshift of the plasmon resonance, but its implications for MIL applying far-field MPM should be further exploited. Here, we explore MIL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 45 publications
2
16
1
Order By: Relevance
“…This in turn increases the probability of a sequential two-photon absorption process when illuminated using focused NIR light from femto-second-pulsed lasers, operating in the tissue transparent wavelength region. [55,56] The resulting multiphoton-induced luminescence (MIL) of the compressed BC-AuNP membranes could be clearly visualized in far-field multiphoton laser scanning microscopy (MPM) (Figure 7a,b and Figure S15, Supporting Information). In contrast, the noncompressed membranes showed no MIL signal (Figure 7a, inset).…”
Section: Nonlinear Optical Effects and Plasmonic Heatingmentioning
confidence: 99%
“…This in turn increases the probability of a sequential two-photon absorption process when illuminated using focused NIR light from femto-second-pulsed lasers, operating in the tissue transparent wavelength region. [55,56] The resulting multiphoton-induced luminescence (MIL) of the compressed BC-AuNP membranes could be clearly visualized in far-field multiphoton laser scanning microscopy (MPM) (Figure 7a,b and Figure S15, Supporting Information). In contrast, the noncompressed membranes showed no MIL signal (Figure 7a, inset).…”
Section: Nonlinear Optical Effects and Plasmonic Heatingmentioning
confidence: 99%
“…The particles are deposited onto different oxide and metal surfaces such as vanadium (V/V 2 O 5 ), silicon dioxide (Si/SiO 2 ), gold (Au), aluminum (Al/Al 2 O 3 ), copper (Cu/CuO) and nickel (Ni/NiO 2 ). The reason for choosing citrate stabilized NPs is due to their availability and broad use in many applications [8,9]. Due to the citrate ligand, further functionalization with functional molecules such as proteins are considered to be straightforward [21,22].…”
mentioning
confidence: 99%
“…However, we found that this approach provided only low image contrast due to a relatively strong background scattering from cellular organelles (data not shown). Previously, it was shown that gold nanoparticles exhibit a strong, shape-dependent TPL that can be used for high-contrast imaging of AuNPs in cells . Therefore, we explored the technique of TPL in which AuNPs are induced to emit light upon two-photon absorption of light from a femtosecond-pulsed laser.…”
Section: Resultsmentioning
confidence: 99%